Camptocormia as a feature of Mc Ardle's disease: A case report - Mathilde Nicolas; Chloé Giret; Sybille Pellieux; Annick Toutain; Anne-Marie Bergemer-Fouquet; Pascal Laforêt; Loic Bouilleau; François Maillot (Molecular Genetics and Metabolism Reports)
Glycogen storage disease type 5 (GSD) is an autosomal recessive metabolic myopathy caused by pathogenic variants in the PYGM gene. We report the case of a patient with typical exercise intolerance with a “second wind” phenomenon, associated with camptocormia which is not commonly recognized as a feature of the disease. Molecular analysis of the PYGM gene the common c.148C > T [p.(Arg50*)] variant and a missense variant in exon 12, c.1471C > T [p.(Arg491Cys)]. GSD 5 and Pompe disease are both glycogen storage diseases in which axial involvement has been described. Although probably underestimated, severe axial myopathy has been rarely reported in GSD 5. We suggest that the long-lasting symptoms associated with camptocormia should be considered as possible initial features of GSD 5.